Problems of Cosmopolitanism and Alternativeness in the History of Central Asia - N. T. Nurulla-Khodzhaeva (MGIMO University Press, 2015)
We residents of Samarkand and Bukhara, throughout history aimed to accumulate traditions of challenging the established (often elitist) limits of local culture, economics and history. The cities communities were under constant pressure of the dichotomy between the notions of nomadism and sedentism, Turkic and Persian speakers. Many community-based units of Samarkand had their own commercial, socio-cultural and educational networks that preserved alternativeness within the life cycle, which balanced between universality and particularism. These lands were dominated by a unique parity, based on Sufi ethics, which designed not syncretic cosmopolitism, but rather introduced the recognition of alternativeness that took into account both similar and diverse waves of ideas. Based on this vision, the author aims to diminish Kantian cosmopolitanism to a level of Euro-American and illustrate the view of cosmopolitanism through a dialogic platform, precisely including its links with the Central Asian versions. Moreover, one cannot identify local cosmopolitanism with the ideas of European Enlightenment, namely individualism and universalism on a global scale. Due to the alternativeness and cosmopolitanism, as well as lack of radical individualism within the local communities, there was no monocultural view on life, since both science and morality (religion, culture, and community) were mutually essential. Nonetheless, present proves that these fields remain their equal vitality to an individual who is capable of simultaneously possessing knowledge about the reality and receiving satisfaction from the reality. This constant motion based on reciprocation was maintained in the ancient culture of Samarkand by two factors: cosmopolitanism and alternativeness.